KORELASI LAMA MENDERITA DIABETES MELLITUS (DM) TIPE 2 DENGAN KEJADIAN NEUROPATI DM PADA PASIEN PROLANIS DI NGEMPLAK, SLEMAN - FERY LUVITA SARI; AGUS TAUFIQURRAHMAN (LP2MTBM MAKARIOZ, 2021)
Diabetic neuropathy is the most commont complication in patients with type 2 diabetes mellitus. Research shows that 60-70% of patients with type 2 DM have diabetic neuropathy and most cases are over 55 years. It stated that longer duration oftype 2 DM, the higher risk of developing diabetic neuropathy. Diabetic patients are members of PROLANIS, so this researchis carried out on PROLANIS patients. To determine the correlation of type 2 diabetes mellitus (DM) duration with diabeticneuropathy incidence in PROLANIS patients in Ngemplak, Sleman. Observational analytic with cross sectional design. Thestudy required subjects with type 2 DM in PROLANIS in Ngemplak, Sleman. The study was conducted by measuring fastingblood glucose levels (BSF),2hour postprandial blood glucose levels,HbA1c levels, DNS and DNE. Thirthy four subjects withbasic characteristics of men are more than women 55,9% and 44,1%. Both age groups are almost the same between >65years and 65 years respectively 52,9% and 47,1%. The results of the bivariate analysis between diabetic neuropathy andthe independent variables were significant in the duration with an OR value of 0,14 (CI 95% 0,02-0,99; p=0,020) and HbA1clevels with an OR value of 0,25 (CI 95% 0,06-1,01; p=0,024). Multivariate analysis was significant on the type 2 DM durationwith an OR value of 0,08 (CI 95% 0,01-0,73; p=0,025). There is a correlation between type 2 Diabetes Mellitus (DM) durationwith diabetic neuropathy incidence in PROLANIS patients in Ngemplak, Sleman.